1987
DOI: 10.1080/03015521.1987.10425574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pasture allowance in winter on liveweight, wool growth, and wool characteristics of Romney ewes

Abstract: In each of two years, pasture allowances of 0.7, 1.2, 1.7, or 2.2 kg dry matter (DM)/ewe per day were offered to groups of Romney ewes for 6 weeks in June -July. The ewes were then run together until weaning in December. In Year I there were 70 2-year-old ewes per group; mean initialliveweight was 47 (SE 0.25) kg. In Year 2 each group comprised 25 2-year-old ewes with a mean initialliveweight of 48 (SE 0.49) kg and 25 6-year-old ewes with a mean initial liveweight of 57 kg. For liveweight change (g/day), the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Herbage utilization rate in this study was higher than that reported by Hawker and Thompson (1987), Carson et al. (2003) and Keady and Hanrahan (2009a,b,c).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Herbage utilization rate in this study was higher than that reported by Hawker and Thompson (1987), Carson et al. (2003) and Keady and Hanrahan (2009a,b,c).…”
Section: Discussioncontrasting
confidence: 78%
“…Hawker and Thompson (1987) also reported a linear increase in herbage intake of pregnant ewes when daily herbage dry‐matter allowance per ewe was increased from 0·7 to 2·2 kg. The absence of a curvilinear relationship in this study is probably associated with the highest herbage allowance offered being only 57% greater than the intake, whereas in the study of Peyraud et al.…”
Section: Discussionmentioning
confidence: 85%